Efficacy and safety of Danhong injection on inflammatory factors and vascular endothelial function in patients with unstable angina pectoris: a systematic review and meta-analysis of randomized clinical trials - Kan, Zunqi; Yan, Wenli; Chen, Cong; Gao, Huanyu; Song, Yongmei (Frontiers in Pharmacology, 2025)
BackgroundInflammatory factors and vascular endothelial damage are significantly involved in the development of unstable angina pectoris (UAP). Danhong injection (DHI) is a compound injection composed of Salvia miltiorrhiza and Carthamus tinctorius extracts. Several clinical studies have demonstrated DHI’s efficacy for treating UAP, with potential pharmacological effects on inflammatory factors and vascular endothelial function. However, to date, the current evidence has not been systematically summarized and analyzed.PurposeThis study provides a comprehensive overview of the most recent clinical findings and systematically analyzes the impact of DHI on inflammatory factors and vascular endothelial function among individuals diagnosed with UAP.MethodsWe searched for randomized controlled trials (RCTs) conducted until January 2023 from two clinical trial registries and eight literature databases. The Cochrane Risk of Bias Tool 2.0 was utilized to assess the potential bias in the included trials, while the GRADE system was employed to evaluate the outcome quality.ResultsWe included 46 trials involving 4,601 patients with UAP. The meta-analysis results suggested that DHI significantly reduced the levels of high-sensitivity C-reactive protein (hs-CRP) (standard mean difference [SMD] = 1.34, 95% confidence interval [CI] [-1.77, −0.90], P < 0.00001), tumor necrosis factor-alpha (TNF-α) (SMD = −0.84, 95% CI [-1.54, −0.15], P = 0.02), interleukin-6 (IL-6) (SMD = −1.05, 95% CI [-1.86, −0.25], P = 0.01), endothelin/endothelin-1 (ET/ET-1) (SMD = −2.01, 95% CI [-2.57, −1.46], P < 0.00001), and homocysteine (Hcy) (SMD = −0.55, 95% CI [-0.71, −0.39], P < 0.00001) but increased the nitric oxide (NO) level (SMD = 1.51, 95% CI [1.04, 1.97], P < 0.00001) in patients with UAP. Twenty-one RCTs described adverse events.ConclusionDHI effectively and safely reduced hs-CRP, TNF-α, IL-6, ET/ET-1, and Hcy levels and increased the NO level in patients with UAP. However, considering the overall low quality of the original studies, future large-scale, high-quality RCTs are imperative to provide robust evidence for clinical practice.Systematic Review Registrationidentifier CRD42023391497.